The effect of internal control and transformational leadership style on employee performance, using work motivation as a moderating variable (Case study of several rural banks (BPR) in Lampung) - Kurniasari, Dwi; Christina, Veronica (WIM Solusi Prima, 2025)
This study aims to identify solutions to the problems faced by Rural Banks (BPR) in Lampung related to low employee performance. The low level of employee performance is presumed to be caused by internal control and transformational leadership factors. The research was conducted at five Rural Banks (BPR) in Lampung, with data collected through questionnaires distributed to 152 operational employees. Of these, 110 responses were returned and deemed suitable for analysis. The data were then analyzed using multiple regression with the Moderated Regression Analysis (MRA) method. The results show that internal control has a significant effect on employee performance, and transformational leadership also significantly influences employee performance. Work motivation is proven to strengthen the relationship between internal control and transformational leadership on employee performance. Based on these findings, the study suggests that companies should strengthen their internal control systems, consistently apply transformational leadership in employee empowerment, and enhance both intrinsic and extrinsic motivation programs to improve employee commitment and productivity.